Wolfberry (Lycium barbarum) Consumption with a Healthy Dietary Pattern Lowers Oxidative Stress in Middle-Aged and Older Adults: A Randomized Controlled Trial - Darel Wee Kiat Toh; Wan Yee Lee; Hanzhang Zhou; Clarinda Nataria Sutanto; Delia Pei Shan Lee; Denise Tan; Jung Eun Kim (MDPI AG, 2021)
Incorporating zeaxanthin-rich wolfberry (Lycium barbarum) into a healthy dietary pattern may augment its antioxidant potential. The present 16-week, parallel design randomized controlled trial aimed to investigate the impact of adhering to a healthy dietary pattern, either with or without whole dried wolfberry (15 g/d) on oxidative stress status (plasma malondialdehyde and 8-iso-prostaglandin F2α) in middle-aged and older adults. Changes to carotenoids status (plasma and skin carotenoids) and body composition were further evaluated to explore potential mechanisms which underlie the antioxidant properties of wolfberry. Plasma 8-iso-prostaglandin F2α, plasma zeaxanthin and skin carotenoids status were significantly raised in the wolfberry consuming group (n = 22; p < 0.05) compared to the control group which showed no changes (n = 18). Likewise in the wolfberry group only, inverse association was observed between the change values of plasma zeaxanthin and plasma 8-iso-prostaglandin F2α (−0.21 (−0.43, 0.00) ng/µmol, regression coefficient (95% CI); p = 0.05). Wolfberry consumption with a healthy dietary pattern may serve as a dietary strategy to attenuate lipid peroxidation among middle-aged and older adults who are at a heightened risk of oxidative stress induced age-related disorders. The antioxidant properties of wolfberry may be attributed to its rich zeaxanthin content.